DIGITAL CONTRACTS: ANALYSIS FROM THE PERSPECTIVE OF ELDERLY PERSONAL PROTECTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Consumer protection is supported by the 1988 Federal Constitution, in Article 5, item XXXII, as a fundamental right guaranteed both individually and collectively. The Consumer Defense Code of 1990 consolidated this right, protecting consumers against abuses in consumer relations. With technological advancement, new issues have emerged, such as the dissemination of misleading advertising on the internet and data breaches. Consequently, there arose a need for greater assurance regarding contractual formalizations carried out virtually. In this context, it has become essential that the information provided be more transparent and guided by good faith. However, the evolution of relationships between consumers and suppliers in the digital age still presents major challenges. Among these issues, special attention is drawn to the relationships established between elderly individuals and financial institutions. In order to prevent abusive or fraudulent practices, the legal framework has been undergoing adaptations. Within this context, one of the debated topics concerns the requirement of physical signatures for elderly individuals in contracts entered into with banks, instead of using digital formats. Through bibliographic and jurisprudential review, employing the explanatory method, this study addresses security and accessibility, the new perception of elderly individuals regarding technology, and the need for solutions that reconcile their protection with digital inclusion and freedom of choice, as well as the regulation of new means of contracting. It concludes that the effective protection of elderly consumers requires harmonizing legal security and digital access, without resulting in technological exclusion.